Arid Environment Perspectives, Challenges and Management - Eyvaz, Murat; Albahnasawi, Ahmed; Gürbulak, Ercan; Tekbaş, Mesut (IntechOpen, 2023)
Aridity is the imbalance between long-term average water supply and long-term average water demand. Arid environments cover more than one-third of the world's land area and represent the most common habitat on Earth after the oceans. Aridity poses a threat to the environment and the economy, and to security, development, food security, and social life around the world. The causes of increased aridity are complex and are thought to be both natural and man-made. The causes of drought include such factors as climate change, population growth, soil erosion, inappropriate irrigation, poor farming methods, soil, water, and groundwater contamination, urbanization, deforestation, improper water management, and desertification of arid and semi-arid zones. This book contains valuable scientific studies on such aspects of aridity as surface and groundwater management, land use, and agricultural applications. Case studies from different geographies and planets are included.